2011
DOI: 10.1186/1752-1947-5-168
|View full text |Cite
|
Sign up to set email alerts
|

Plasmablastic lymphoma in the ano-rectal junction presenting in an immunocompetent man: a case report

Abstract: IntroductionPlasmablastic lymphoma is an aggressive non-Hodgkin lymphoma classically occurring in individuals infected with HIV. Plasmablastic lymphoma has a predilection for the oral cavity and jaw. However, recent case reports have shown lymphoma in the stomach, lung, nasal cavity, cervical lymph nodes and jejunum in HIV-negative individuals. We report what is, to the best of our knowledge, the first case of plasmablastic lymphoma occurring in the ano-rectal junction of an HIV-negative man.Case PresentationA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
3
29
0
1
Order By: Relevance
“…Reactivation of EBV infection in states of relative immunosuppression can cause unmasking of some clones of B-cells at the sites of long standing chronic inflammation. A similar case of anal PBL has been described in HIV negative patient with a history of ischiorectal abscess and anal fistula [7] . A close follow up should be advised in HIV infected patients with similar chronic mucocutaneous inflammatory lesions while keeping in mind the possibility of lymphomatous transformation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Reactivation of EBV infection in states of relative immunosuppression can cause unmasking of some clones of B-cells at the sites of long standing chronic inflammation. A similar case of anal PBL has been described in HIV negative patient with a history of ischiorectal abscess and anal fistula [7] . A close follow up should be advised in HIV infected patients with similar chronic mucocutaneous inflammatory lesions while keeping in mind the possibility of lymphomatous transformation.…”
Section: Discussionsupporting
confidence: 62%
“…In our case, this patient developed PBL 18 years after the initial infection. The CD4 counts are usually less than 200/mm 3 at the time of presentation [7] . Our patient had a CD4 count of 363/mm 3 at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, upon review, in fact, we found it to be the most common site for EoPL, with a total of 12 cases being identified from the available literature [6,16,17,20,21,22,23]. The other common sites include the stomach, skin, cervical lymph node and orbit, with a similar incidence [10,11,15,17,24,25,26,27,28,29,30,31,32,33,34].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Since its initial report in the oral cavity in patients with HIV in 1997 , PBL has been found to occur outside of the oral cavity in both HIV-infected and uninfected patients. It has been reported to arise in the retroorbit (Liu et al 2011 ), nasal cavity (Liu et al 2011 ); jaw (Liu et al 2011 ); parotid gland (Bishop and Westra 2010 ); larynx (Stephenson et al 2013 ); bone marrow (Liu et al 2011 ;Chuah et al 2009 ); lung (Chuah et al 2009 ); gastrointestinal tract including esophagus (Mani et al 2008 ), stomach, small intestine (Cha et al 2010 ;Wang et al 2012 ), colon (Liu et al 2011 ), and ano-rectal region (Brahmania et al 2011 ); liver (Tani et al 2013 ); retroperitoneum (Dholaria et al 2012 ); testis (Sagues et al 2012 ); penis ; vulva (Chabay et al 2009 ); skin (Tiong et al 2013 ), and bone (Liu et al 2011 ). Central nervous system (CNS) involvement including the orbit, leptomeninges, and parenchyma as well as peripheral nervous system involvement has been reported to occur with systemic disease at time of diagnosis, or at time of relapse (Ustun et al 2009 ;Zhang et al 2012 ;Gao et al 2013 ).…”
Section: Clinical Presentationmentioning
confidence: 99%